Socio-demographic Factors Associated with Diet Quality Among a Cohort of People Living with HIV (P04-075-19). (13th June 2019) - Sackey, Joachim; Wang, Grace; Wanke, Christine; Tang, Alice; Knox, Tamsin
Abstract: Objectives: To identify social, demographic and health factors associated with diet quality over time in a community-dwelling population of people living with HIV (PLHIV) in the Greater-Boston area. Methods: Secondary analysis of data from the Cardiovascular Assessment Risk Examination (CARE) prospective cohort study carried out between 2007 and 2013. The study included 288 PLHIV recruited from the Greater-Boston area with study visits annually. Repeated measures linear regression models with diet quality [assessed using Healthy Eating Index (HEI-2010)] as the dependent variable was used to analyze the data. The HEI-2010 ranges from 0–100 with a higher score indicating higher diet quality. Results: At baseline, study participants were mostly male (73%), 51 ± 7 years, unemployed (56%) and White (51%). They had been living with HIV for an average of 16years with an average CD4 count of 520 cells/mm3. Approximately one third reported being depressed (35%), being food insecure (37%), and binge drinking in the previous 6 months (30%). The mean HEI-2010 score at baseline was 48.7 ± 16.2 with male participants having a higher score (50.5) than females (43.7) ( P = 0.004). Longer duration of highly active antiretroviral therapy (HAART), having an undetectable viral load, being food secure, fewer pack-years of smoking, and increasing age were independently associated with higher diet quality over time ( P < 0.0001). There were no significant interactions between time and the significant independent variables. Conclusions: Among this cohort of PLHIV, several sociodemographic and clinical factors were associated with higher diet quality. Interventions to improve diet quality in PLHIV should focus on younger people and those who are food insecure. In addition, clinicians should continue to push for treatment adherence and viral suppression, along with curtailing smoking. With improved long term survival due to HAART, assessment of food security and diet quality may reduce cardiometabolic risk factors and further improve mortality. Funding Sources: National Heart, Lung, And Blood Institute.